Non-Negativity of Nominal and Real Riskless Rates, Arbitrage Theory, and the Null-Alternative Cash - Jochen Wilhelm; Bernhard Nietert (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2004)
Pragmatic-world nominal riskless rates are non-negative. However, conventional arbitrage theory has yet to develop a theoretical justification of this phenomenon. – We define the null-alternative cash as an investor holding onto cash and refraining from investment and consumption ("doing nothing"); we use the null-alternative cash to prove that both nominal spot and nominal forward rates are non-negative and that prices of zero-coupon bonds do not increase with increasing maturity. In a positive inflation environment, however, both real spot and real forward rates might well become negative, but prices of zero-coupon bonds still do not increase with increasing maturity.
Keywords: G10; G12; 650; arbitrage theory; inflation; non-negativity of spot and forward rates; short selling constraints; Arbitrage Pricing; Inflation; Zins; Zinstermingeschäft; Theorie